ARI updates 2014 / Accounting Research Institute (Accounting Research Institute (ARI), 2014)
First and foremost I would like to extend my heartiest congratulations to the Accounting Research Institute (ARI) for yet another remarkable year. Indeed, the year 2014 had witnessed momentous accomplishments for ARI, putting it on the world map in the realm of Islamic finance. This could be seen through its achievements, among which was being selected as one of the winners for the prestigious Global Islamic Finance Award (GIFA) 2014.